Modeling Influence Tribal Coalitions in Kenya Presidential Politics: A Case Study of Kikuyu-Kalenjin versus Luo-Kamba - Ngari, Cyrus G. (Science Domain International, 2016)
A deterministic model was developed to describe the two dominant tribal coalition based voting bloc (A and B) and other tribes (C). The first order nonlinear ordinary differential equations were deduced using predator-prey equations. The system was established to lie in feasible region. The coalition free steady state was determined. The conditions necessary for local stabilities of steady states were determined using Routh-Hurwitz criteria for stability. The condition necessary for global stability of steady state were determined using Lyapunov function. The estimated numerical bound of the registered voters was obtained as 27871013. Numerical simulation was carried out using 2013 general election scenario.
Keywords: Predator-prey; Routh-Hurwitz; Lyapunov; bound; simulation